Antioxidant and Antiulcer Activities of Methanolic extract of Alternenthra pungens - Meera, R.; Devi, P. (Asian Journal of Chemistry, 2010)
In this paper, in vitro antioxidant and in vivo antiulcer activites of methanolic extract of Alternenthra pungens. Antioxidant activity was determined by two in vitro methods-DPPH and H2O2 radical scavenging. To study the antiulcer activity of methanolic extract of Alternenthra pungens (100 and 200 mg/Kg) using different models of ulceration in rats viz., aspirin induced ulcer and cold restraint stress induced gastric lesions in rats. While in aspirin and cold restraint stress induced models, ulcer index and % inhibition of gastric ulcers was determined. Famotidine (20 mg/Kg) was used as a reference drug. Methanolic extract of Alternenthra pungens treated animals exhibited protective effect on ulceration induced by aspirin induced ulcer and cold restraint stress in rats. Control animals had ulcers, while animal treated with methanolic extract of Alternenthra pungens showed reduction in ulcers in the models in a dose dependent manner; it significantly (p < 0.001) decreased the volume of gastric acid secretion and also reduced with respect to control and comparable to the standard drug.